2017
DOI: 10.1111/kykl.12145
|View full text |Cite
|
Sign up to set email alerts
|

Online Networks and Subjective Well‐Being

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 118 publications
(189 reference statements)
3
54
2
1
Order By: Relevance
“…• First, studies use different measures of SWB, including positive measures such as life satisfaction and happiness (Katsamanis 2006;Kavetsos and Koutroumpis 2011;Kross et al 2013;Lelkes 2013;Pénard et al 2013;Sabatini and Sarracino 2014;Shotwell 2002) and negative measures such as depression or loneliness (Amichai-Hamburger and Ben- Bakken et al 2008;Bessiere et al 2010;Campbell et al 2006;Cotten et al 2012;Ford and Ford 2009;Fortson et al 2007;Franzen 2000;Kraut et al 1998;Morrison and Gore 2010;Nimrod 2013;Shaw and Gant 2002;Tandoc et al 2015). We are unaware of any studies that use both positive and negative measures except for Stepanikova et al (2010), who employ life satisfaction and loneliness as SWB proxies in the hope of shedding light on their simultaneous effects on individual well-being.…”
Section: Prior Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…• First, studies use different measures of SWB, including positive measures such as life satisfaction and happiness (Katsamanis 2006;Kavetsos and Koutroumpis 2011;Kross et al 2013;Lelkes 2013;Pénard et al 2013;Sabatini and Sarracino 2014;Shotwell 2002) and negative measures such as depression or loneliness (Amichai-Hamburger and Ben- Bakken et al 2008;Bessiere et al 2010;Campbell et al 2006;Cotten et al 2012;Ford and Ford 2009;Fortson et al 2007;Franzen 2000;Kraut et al 1998;Morrison and Gore 2010;Nimrod 2013;Shaw and Gant 2002;Tandoc et al 2015). We are unaware of any studies that use both positive and negative measures except for Stepanikova et al (2010), who employ life satisfaction and loneliness as SWB proxies in the hope of shedding light on their simultaneous effects on individual well-being.…”
Section: Prior Studiesmentioning
confidence: 99%
“…The studies that employ a macro approach are numerous and include, for example, the work of Amichai-Hamburger and Ben-Artzi (2003), Bakken et al (2008), Campbell et al (2006), Ceyhan and Ceyhan (2008), Cotten et al (2012), Franzen (2000), Ford and Ford (2009), Katsamanis (2006), Kraut et al (1998), Kross et al (2013), Lelkes (2013), Pénard et al (2013), Sabatini and Sarracino (2014), Tandoc et al (2015), and Wickramasinghe and Ahmad (2013). Those using a micro approach, however, are somewhat fewer (see, for example, Bessiere et al 2010;Cotten et al 2011;Fortson et al 2007; Morrison and Gore 2010;Nimrod 2013;Stepanikova et al 2010).…”
Section: Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different researches have shown negative effect of heavy SNS use and depression [1], anxiety [2], histrionic personality, [3] and addiction and dependency [4]. Having this in mind, the widespread use of SNSs and particularly Facebook [4] among youths should raise some crucial attention.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the relationship of Facebook use and the social capital it was found that intensity of Facebook was related to life satisfaction, social trust, civic engagement, political participation [38], higher motivation [39], and also to psychological well-being [18], whereas others found contradictory results on the association of social networking with individual welfare [40]. However, from a critical point of view, there are also reports on the subjective overestimation of competences discussed as the Dunning-Kruger effect [41,42] and there are also reports of decreased academic achievement associated with social networking [29].…”
mentioning
confidence: 99%